An Analysis of Illocutionary Act Spoken by The Contestants of Semi-Finale Service Challenge, Australia MasterChef Season 13 - Dewi, Putu Riska Yulvani; Utami, Ni Putu Cahyani Putri (Journal of Linguistic and Literature Studies, 2025)
This study analyzed the frequency and types of illocutionary acts spoken by contestants during the Semi-Finale Service Challenge of Australia MasterChef Season 13, using Searle's (1979) theory about the type of illocutionary act. The data collected from the Contestant utterances on the Australia MasterChef Season 13 when accomplishing a mission, explaining the dish or situation, and talk to judges or another contestant. This study used qualitative methods to analyze the illocutionary act spoken by the contestant during the competition and describe the data with literal explanation.  The result found the Assertive Illocutionary Act was the most dominant uses occur 92 or 54% data, the second frequently uses in the Directive Illocutionary Act occur 35 or 20 % data, and followed by the Commissive Illocutionary Act occur 23 or 13% data, the next is Expressive Illocutionary Act that occur 19 or 11% data, and the last position is the Declarative Illocutionary Act that consist 3 or 2% data. This study highlights the contestants use of language to describe, command, promise, express emotions, and declare states in a high-stress culinary competition setting. The implication of this research provided the understanding of the illocutionary act in daily live and the impact or the power of illocutionary act on conversation.